2015
DOI: 10.1016/j.bmc.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric derivatives of functionalized amino acids and α-aminoamides: Compounds with anticonvulsant activity in seizure models and inhibitory actions on central, peripheral, and cardiac isoforms of voltage-gated sodium channels

Abstract: Six novel 3″-substituted (R)-N-(phenoxybenzyl) 2-N-acetamido-3-methoxypropionamides were prepared and then assessed using whole-cell, patch-clamp electrophysiology for their anticonvulsant activities in animal seizure models and for their sodium channel activities. We found compounds with various substituents at the terminal aromatic ring that had excellent anticonvulsant activity. Of these compounds, (R)-N-4′-((3″-chloro)phenoxy)benzyl 2-N-acetamido-3-methoxypropionamide ((R)-5) and (R)-N-4′-((3″-trifluoromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In order to obtain compounds 8-11 and 17, the ester groups of compounds IIa-IId were hydrolysed with 10% NaHCO 3 (8 and 9) at room temperature (6-8 h) or were subjected to aminolysis with use of NH 3(aq conc) (10,17) or methylamine (11) with the addition of methanol. The precipitated final products were recrystallized from a hexane-toluene (1 : 1) mixture.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain compounds 8-11 and 17, the ester groups of compounds IIa-IId were hydrolysed with 10% NaHCO 3 (8 and 9) at room temperature (6-8 h) or were subjected to aminolysis with use of NH 3(aq conc) (10,17) or methylamine (11) with the addition of methanol. The precipitated final products were recrystallized from a hexane-toluene (1 : 1) mixture.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the extracts (−)-HDA and HTA had effects on different sodium channels subtypes, we examined the effects of these compounds at a 20 μM concentration on peak current, steady-state activation, and fast inactivation in human embryonic kidney 293 (HEK293) cells that stably expressed cardiac (hNav1.5) and central nervous system (hNav1.1, rNav1.3) channels using voltage protocols previously reported . We observed that (−)-HDA had inhibitory effects on all NaV1.x currents tested; representative currents are shown in Figure A, E, and I (Figure B, C, NaV1.1:0.1% DMSO: −57.2 ± 9.2 mV versus (−)-HDA: −30.1 ± 5.1 mV; Figure F, G, NaV1.3:0.1% DMSO: −99.8 ± 14.6 mV versus (−)-HDA: −45.4 ± 6.3 mV; Figure J, K, NaV1.5:0.1% DMSO: −571.1 ± 86.6 mV versus (−)-HDA: −330.8 ± 60.9 mV).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Amino acid derivatives have been reported to be biologically active as antibacterials, [14][15][16] antifungals 17,18 and antioxidants, 19 pseudo-analogues of the naturally occurring antibiotic sparsomyci, 20 anti-inflammatory 21 and anti-convulsant 22 agents. They are used also as reactive substrates in the design of bioactive molecules for cancer treatment.…”
mentioning
confidence: 99%